Pendampingan Pengelolaan Keuangan, Perpajakan, dan Kewirausahaan Yatim Center Al-Ruhamaa’ - Megawati, Lokita Rizky; Winarningsih, Srihadi; Zarkasyi, Wahyudin; Sukmadilaga, Citra (Jurnal Pusat Inovasi Masyarakat, 2024)
Over the past decade, social organizations in Indonesia have faced increasingly complex challenges related to financial management, taxation, and entrepreneurship development. Yatim Center Al-Ruhamaa', as an amil institution focused on the welfare of orphans and the poor, is no exception. Challenges such as non-standard financial record-keeping, manual tax reporting, limited utilization of waqf funds, and the lack of diversification in business activities have become key issues requiring innovative and sustainable solutions. Financial and entrepreneurship assistance has proven to be an effective approach to improving the management and independence of amil institutions. The objectives of this activity are to 1) Establish a standardized and efficient financial recording system; 2) Facilitate the online tax reporting process; 3) Optimize the utilization of waqf funds for investment; and 4) Support the diversification of business activities at Yatim Center Al-Ruhamaa’. A qualitative approach was employed to examine the process of developing standard financial recording formats, improving financial records, EFIN registration, waqf fund management, and business activity diversification. The results of this initiative show significant improvements in financial management and entrepreneurship at Yatim Center, providing insights into best practices and recommendations for similar organizations. The conclusion of this mentoring process has successfully enhanced the efficiency of financial management and entrepreneurship, leading to greater transparency and sustainability of the institution.